'Nobody is forgotten, nothing is forgotten': Cultural sustainability in ruptured landscapes in Estonia. Issue 3 (27th May 2017) - Sooväli-Sepping, Helen
ABSTRACT: The author considers landscape heritage from a cultural sustainability perspective in order to develop an understanding of genealogy, cultural politics, and practices of the World War II heritage construction in the Soviet Union. The primary research question was: What were the mechanisms of heritage construction from a mnemohistoric point of view, as conceptualised by Jan Assmann? With this in mind, a detailed investigation analysis of Soviet World War II memorials in Estonia was performed, taking into account examples of Soviet propaganda texts, visual representations, and war commemoration practices, as well as site visits to commemoration places. The analysis traces social change as landscapes of rupture. One outcome considered is cultural sustainability as a strategy for social cohesion in situations in which a landscape heritage discourse changes. The author concludes that multiethnic societies may see new opportunities to find common values in forgotten landscape heritage.